Phytochemical analysis, antioxidant and antibacterial efficacy of methanol and hexane extract of Centella asiatica - Pokhrel, Shanta; Neupane, Prabha (BIBECHANA, 2021)
Centella asiatica is well known for its anti-inflammatory, anticancer, antioxidant, antimicrobial, analgesic, diuretic properties. Its hexane and methanol extracts were screened for the presence of phytoconstituents as well as their antibacterial and antioxidant activity. The phytochemical screening showed the presence of carbohydrate, glycosides, flavonoids, phenolic compound, alkaloids, and saponin. The methanol extract showed more effective antibacterial activity against salmonella typhi. Antioxidant activity of methanol extract was evaluated by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity showed potent antioxidant activities with IC50 value 3.74 μg/mL slightly higher than standard ascorbic acid (IC50 = 2.576 μg/mL). The present study indicates that the tested plant can be an important source of antibacterial agents and recommends that the active phytoconstituents be isolated, identified, and screened individually for activities and also subjected further for in vivo and toxicological studies. BIBECHANA 18 (2) (2021) 18-25